Metode active listening: Active listening - Norpi (Ra'ah: Journal of Sociology of Religion, 2022)
T Human trafficking, in this case, the sale of underage children with the aim of becoming commercial sex works, starting with the mode or the lure of being given jobs, not only in cities or metropolitan areas. However, it targets more remote areas, hinterlands and undevelopend areas because it is considered easier for perperators to find victim. The legal rules regarding human trafficking have been regulated in the criminal Code (KUHP) Article 297 and Law no. 21 of 2007 cobcerning the eradication of the criminal Act of Traffing in Persons in Article 1 Paragraph (1) with the threat of a maximum sentence of six years in prison. However, this research is more about the background of the perpetrator/defendant commingtting the crime because everthing has a background and this cannot be separated from how he individual’s past and now the environment influences behavior. Being in a narrow space and every movement space is limited will have an impact on the psyche of every prisoner/prisoner, but the rules are still rules that must be obeyed, as well as actions that violate will be held accountable whether or not the time is good. An active listening methods is needed as an effort to all they are still people who are accepted in all their circumstance. Thus they are able to realize more self-intropection.